Avaliação da mobilidade urbana e das áreas verdes do município de João Pessoa, Paraíba: perspectivas para uma cidade sustentável - Fernandes, Hélder Formiga (2018)
The objective of this research was to evaluate the Urban Mobility and the Green Areas of the Municipality of João Pessoa, in the perspective of the development of a sustainable city. The theoretical basis of the research was elaborated with the aid of the norm ABNT NBR ISO 37.120:2017, which gives the necessary parameters to evaluate the sustainable development of communities. Periodic visits were made to the Secretaria de Mobilidade Urbana (SEMOB) and the Secretaria de Meio Ambiente (SEMAM) of the Municipality of João Pessoa, as well as the Superintendência de Administração de Meio Ambiente (SUDEMA) and the e no Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis (IBAMA/PB), to obtain official documents for analysis, how visits were made in various sectors of the city to map out the green areas of the municipality and evaluate its main Urban Mobility Programs. Questionnaires were also developed, which were answered by randomly chosen people. It was verified that the Municipality of João Pessoa has been carrying out Projects of Sustainable Urban Infrastructure, interventions in various sectors of the city, including asphaltic capping, widening of roads, installation of cycle paths, lowering of pavements, exclusive lanes for buses, improving mobility of the population. Although the efforts of the city council to facilitate urban mobility in the Municipality of João Pessoa are notorious, most respondents informed that the excess of vehicles is the greatest difficulty for road dislocations. In addition, the poor quality of the buses and the waiting time of more than 30 minutes discourage the use of this type of transportation, making João Pessoa a city that uses the urban automobile-road model for the mobility of the population. Regarding the green areas, Mata do Buraquinho, Parque Arruda Câmara and the Praça da Independência are frequented by a large portion of the population. The majority of the respondents recognized that the Municipality of João Pessoa as a green city, being prepared to receive the title of sustainable city. It is concluded that the Municipality of João Pessoa is conducting urban mobility projects and in the green areas, transforming it into a sustainable city.